Studies on interaction of oligoadenylates with proteins in vitro by MALDI-TOF mass spectrometry - Levchenko, S.M.; Rebriev, A.V.; Tkachuk, V.V.; Dubey, L.V.; Dubey, I.Ya.; Tkachuk, Z.Yu. (Вiopolymers and Cell, 2013)
Aim. To investigate the ability of «core» 2'-5'- and 3'-5'-oligoadenylates (OA) to interact with α-interferon – a key protein of the 2'- 5'-OAS/RNAase L system responsible for antiviral cell defense. Methods. MALDI-TOF mass spectrometry was used in the studies on protein-ligand interactions. Results. It was shown that 2'-5'-A3 and its epoxy-modified analog 2'-5'-A3-epo can bind to α-interferon in vitro. 3'-5'-tri- adenylate is also capable of binding to this protein. One to five ligand molecules can bind simultaneously to the molecule of α-interferon. At the same time, all studied oligonucleotides do not bind to insulin. Conclusions. It was established that «core» 2'-5'- and 3'-5'-triadenylates are capable of multiple interaction with α-interferon to form stable complexes. However, they do not bind to insulin which is not involved in the 2'-5'-OAS/RNAase L system.